Gendered perspective of informal sector of the economy in Pakistan - Syeda Mahnaz Hassan; Fatima Farooq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This research paper examined gendered perspective of informal economy of Pakistan and has tried to highlight the gender discriminatory practices which home based women workers are facing. The paper mainly focuses on the gendered ideology of work prevailing in the society and other disparities which these women workers face due to being female. The mixed mode methodology was used to collect primary data from the four different sectors. The respondents of the study were home based women workers who were selected through purposive sampling process. The findings of the primary research revealed the worst condition of gender discriminatory practices, such as, exploitation (93.3%), behavioral problems (67%) and restricted mobility (73%), against home based women workers due to specific socio-cultural build-up of the society. On the basis of the study findings, a comprehensive table exhibiting life cycle risks of home based women workers was presented to identify the gendered perceptions existing in the society. Finally, the paper concludes that while designing interventions and formulating policies, gender dimensions and gender norms must not be ignored, in order to attain fruitful results and material and social welfare of the society.
Keywords: 330; gender discrimination; gender disparity; home based women workers; informal sector of economy